Iperione “reloaded” o la dinamica della (ri)traduzione (Studia theodisca, 2017)
This paper presents the aims and characteristics of a new translation of Hyperion (Milano 2015). The translator moves from a wide notion of “text” and tries to acquaint the reader not only with the text itself and its semantic and syntactical structures, but also with text-external elements, such as the different phases of the opera’s development assembled into an appendix and translated for the first time into Italian. These elements include also a dense network of other philosophical and literary works the author is interacting with in his novel. Examples are given to set out and illustrate the most important translation strategies used.